2018
DOI: 10.1111/jeb.13387
|View full text |Cite
|
Sign up to set email alerts
|

Weak and inconsistent associations between melanic darkness and fitness‐related traits in an insect

Abstract: The idea that the fitness value of body coloration may be affected by biochemically mediated trade‐offs has received much research attention. For example, melanization is believed to interact with other fitness‐related traits via competition for substrates, costs associated with the synthesis of melanin or pleiotropic effects of the involved genes. However, genetic correlations between coloration and fitness‐related traits remain poorly understood. Here, we present a quantitative‐genetic study of a coloration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A study of polymorphic alpine weta Hemideina maori suggested that common immune expression was not heightened with dark coloration. The authors noted that the previous finding of a stronger immune response associated with dark coloration in the high‐density melanic phase of polyphonic insects cannot be extended to insects with other forms of discrete color variation (Sandre et al., 2018). A weak relationship was found between cuticular melanism and the fitness of mountain stone weta Ematurga atomaria , which does not support a universal trade‐off relationship between body coloration and fitness, suggesting that cuticular biological cost does not necessarily interfere with adaptive evolution (Robb et al., 2003).…”
Section: Discussionmentioning
confidence: 98%
“…A study of polymorphic alpine weta Hemideina maori suggested that common immune expression was not heightened with dark coloration. The authors noted that the previous finding of a stronger immune response associated with dark coloration in the high‐density melanic phase of polyphonic insects cannot be extended to insects with other forms of discrete color variation (Sandre et al., 2018). A weak relationship was found between cuticular melanism and the fitness of mountain stone weta Ematurga atomaria , which does not support a universal trade‐off relationship between body coloration and fitness, suggesting that cuticular biological cost does not necessarily interfere with adaptive evolution (Robb et al., 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Although tyrosine can be synthesized from phenylalanine, this synthesis itself may not be cost‐free and there is evidence from both mammals and insects that supplementary tyrosine can affect melanization (Evison et al., 2017 ; Morris et al., 2002 ; Watson et al., 2018 ). Indirect evidence for melanin‐synthesis costs in insects also comes from studies that find negative phenotypic (or sometimes genetic) correlations between various melanin‐based traits such as color and immune defense or between melanin‐based traits and other fitness components (Busso et al., 2017 ; Kangassalo et al., 2016 ; Moore et al., 2018 ; Roff & Fairbairn, 2013 ; Sun et al., 2018 , but see also Sandre et al., 2018 ). In the present study, increased dietary tyrosine increased melanization of the spots in cabbage white butterflies therefore adding additional support to the hypothesis of costly melanin‐synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The offspring of the resulting half-sib and full-sib families were divided between two host plants: 12 larvae from each brood were reared on bilberry and three on heather. Using two different host plants was motivated in the context of other uses of the data set [43, 45, 46]. The larvae (N = 1379 reaching pupation) were reared individually in transparent 50 ml plastic vials at 22°C, exposed to a light/dark cycle of 16L:8D, and being provided with food ad libitum .…”
Section: Methodsmentioning
confidence: 99%